2020
DOI: 10.1002/jbt.22564
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ellagic acid on spinal cord and sciatica function in a mice model of multiple sclerosis

Abstract: Multiple sclerosis (MS) is a well‐known neurodegenerative disorder, causing toxicity in different organs, such as spinal cord tissue. The goal of this study was to investigate the protective effect of ellagic acid (EA) against spinal cord and sciatica function in cuprizone (Cup)‐induced demyelination model. Animals were divided into six equal groups. The first group received tap water as the control. Cup group was treated with Cup (0.2% w/w in fed). EA 100 group was orally treated with EA (100 mg/kg). EA + Cup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…SOD, CAT, and glutathione peroxidase are primary antioxidants involved in the direct ROS mechanism while glutathione is considered as a secondary antioxidant that cooperates in the ROS detoxification via reducing peroxide levels [ 59 , 60 ]. The current study has reported that the levels of various antioxidants including SOD, CAT, GSH have been drastically decreased at disease induction in all groups as evident from previous studies [ 61 , 62 ] and their levels were significantly restored after treatment with the selected plant extracts which is concurrent with the study of Kumar et al [ 63 ]. GPx in the MS individual’s erythrocytes continues undistinguishable meanwhile contradictory data about its activity [ 64 ].…”
Section: Discussionsupporting
confidence: 87%
“…SOD, CAT, and glutathione peroxidase are primary antioxidants involved in the direct ROS mechanism while glutathione is considered as a secondary antioxidant that cooperates in the ROS detoxification via reducing peroxide levels [ 59 , 60 ]. The current study has reported that the levels of various antioxidants including SOD, CAT, GSH have been drastically decreased at disease induction in all groups as evident from previous studies [ 61 , 62 ] and their levels were significantly restored after treatment with the selected plant extracts which is concurrent with the study of Kumar et al [ 63 ]. GPx in the MS individual’s erythrocytes continues undistinguishable meanwhile contradictory data about its activity [ 64 ].…”
Section: Discussionsupporting
confidence: 87%
“…The activities of SOD and CAT were measured using a Nasdox and Nactaz kit (NavandSalamat, Iran), respectively, and according to the kit's instruction. The enzyme activities were expressed as U/mg protein [ 8 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The protein accumulation hypothesis indicated that the accumulation of improperly folded proteins such as amyloid-beta (A β ) and neurofibrillary tangle in the brain of people with Alzheimer's disease cause oxidative stress and inflammatory damage, which ultimately leads to synaptic dysfunction [ 6 ]. Reactive oxygen species (ROS) are free radicals, derived from oxygen, which have been shown to play a role in cell damage [ 7 , 8 ]. They are produced naturally during mitochondrial respiration and energy production, but normally, they are neutralized by the cellular antioxidant defense systems [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acute and subchronical neurotoxicity was evaluated through rotarod test, which assesses ataxia and motorial impairment, two signs of neurological damage [ 24 ]. In our study, acute intraperitoneal administrations of all forms of thioctic acid were toxic at 360 and 480 µmol/kg (corresponding to 75 mg/kg and 100 mg/kg of racemic form) because they similarly altered neurological and motorial capabilities of the rodents in all groups of treatment; (+/−) and (+) thioctic acid decreased time of walking at 360 and 480 µmol/kg, while (−) thioctic acid only at 480 µmol/kg.…”
Section: Discussionmentioning
confidence: 99%